Celiac Artery Flow Pattern in Infants with Single Right Ventricle Following the Norwood Procedure with a Modified Blalock-Taussig or Right Ventricle to Pulmonary Artery Shunt - Johnson, Jason N. (2011)
A potential advantage of the right ventricle to pulmonary artery versus modified Blalock–Taussig shunt in patients undergoing the Norwood procedure is limitation of diastolic runoff from the systemic to pulmonary circulation. We evaluated mesenteric flow patterns and gastrointestinal outcomes following the Norwood procedure associated with either shunt type. Patients randomized to a right ventricle to pulmonary artery versus modified Blalock–Taussig shunt in the Pediatric Heart Network Single Ventricle Reconstruction Trial at centers participating in this ancillary study were eligible for inclusion; those with active necrotizing enterocolitis, sepsis, or end-organ dysfunction were excluded. Celiac artery flow characteristics and gastrointestinal outcomes were collected at discharge. Forty-four patients (five centers) were included. Median age at surgery was 5 days [interquartile range (IQR) = 4–8 days]. Median celiac artery resistive index (an indicator of resistance to perfusion) was higher in the modified Blalock–Taussig shunt group (n = 19) versus the right ventricle to pulmonary artery shunt group (n = 25) [1.00 (IQR = 0.84–1.14) vs. 0.82 (IQR = 0.74–1.00), p = 0.02]. There was no difference in interstage weight gain, necrotizing enterocolitis, or feeding intolerance episodes between the groups. The celiac artery resistive index was higher in patients with the modified Blalock–Taussig shunt versus the right ventricle to pulmonary artery shunt but was not associated with measured gastrointestinal outcomes.